Islam, gender, & social change - Haddad, Yvonne Yazbeck, 1935-; Esposito, John L. (Oxford University Press, 1998)
"The essays collected in this book place this issue in its historical context and offer case studies of Muslim societies from North Africa to Southeast Asia. These fascinating studies shed light on the impact of the Islamic resurgence on gender issues in Iran, Egypt, Jordan, Pakistan, Oman, Bahrain, the Philippines, and Kuwait. Taken together, the essays reveal the wide variety that exists among Muslim societies and believers, and the complexity of the issues under consideration. They show that new things are happening for women across the Islamic world, and are in many cases being initiated by women themselves. The volume as a whole militates against the stereotype of Muslim women as repressed, passive, and without initiative, while acknowledging the very real obstacles to women's initiatives in most of these societies."--Jacket